2012
DOI: 10.1055/s-0032-1322540
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Children Undergoing Surgery for Congenital Heart Disease

Abstract: Acute kidney injury (AKI) is a serious postoperative complication in children undergoing surgery for congenital heart disease. The incidence of this complication and its consequences may have changed due to advances in surgical technique, but comparisons between studies are compromised by differences in study design, diagnostic criteria, and patient selection. Recently, attention has been drawn to the importance of an early diagnosis based on the use of new, refined, and sensitive biomarkers. However, the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…8 However, pRIFLE may have lower specificity in the case of severe kidney injury. Nevertheless, most AKI patients in the present study developed only mild kidney injury and all patients had nearly fully recovered prior to discharge.…”
Section: Variables Affecting Aki Severitymentioning
confidence: 99%
“…8 However, pRIFLE may have lower specificity in the case of severe kidney injury. Nevertheless, most AKI patients in the present study developed only mild kidney injury and all patients had nearly fully recovered prior to discharge.…”
Section: Variables Affecting Aki Severitymentioning
confidence: 99%
“…Acute kidney injury (AKI) occurs in up to 50% of children after cardiopulmonary bypass (CPB), 1,2 and is independently associated with adverse outcomes, including longer lengths of stay (LOSs), prolonged mechanical ventilation, and higher mortality. 3,4 Early identification of patients at risk for developing AKI may allow implementation of strategies to reduce related morbidity and mortality.…”
Section: What This Study Addsmentioning
confidence: 99%
“…5,6 Preliminary evidence suggests that biomarkers can help to identify patients at risk for postoperative AKI. 2 In both pediatric and adult populations, renal biomarkers, such as serum cystatin C and neutrophil gelatinase-associated lipocalin (NGAL), have been shown to predict postoperative AKI and improve risk classification when combined with other clinical models. [7][8][9][10][11] In addition, studies in adults have shown that pre-and postoperative levels of cardiac biomarkers, such as B-type natriuretic peptide (BNP), strongly predict postoperative AKI risk.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Acute kidney injury (AKI) occurs in up to 50% of children after cardiopulmonary bypass (CPB), 1,2 and is independently associated with adverse outcomes, including longer lengths of stay (LOSs), prolonged mechanical ventilation, and higher mortality. 3,4 Early identification of patients at risk for developing AKI may allow implementation of strategies to reduce related morbidity and mortality.…”
Section: What This Study Addsmentioning
confidence: 99%
“…5,6 Preliminary evidence suggests that biomarkers can help to identify patients at risk for postoperative AKI. 2 In both pediatric and adult populations, renal biomarkers, such as serum cystatin C and neutrophil gelatinase-associated lipocalin (NGAL), have been shown to predict postoperative AKI and improve risk classification when combined with other clinical models. [7][8][9][10][11] In addition, studies in adults have shown that pre-and postoperative levels of cardiac biomarkers, such as B-type natriuretic peptide (BNP), strongly predict postoperative AKI risk.…”
Section: What This Study Addsmentioning
confidence: 99%